2022
DOI: 10.1111/are.15872
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal, histopathological and genotoxic effects of Scenedesmus obliquus and Spirulina platensis extracts and their biosynthesized zinc oxide nanoparticles on Biomphalaria alexandrina snails

Abstract: Searching for molluscicidal agents of biological origin is mandatory to avoid the drawbacks of using chemical molluscicides. Algae are good candidates as sources of compounds with molluscicidal properties, especially if they are combined with modern techniques such as nanotechnology. This study aimed to evaluate the molluscicidal activity of two algal extracts and their biosynthesized zinc oxide nanoparticles (ZnONPs) on Biomphalaria alexandrina snails. The results indicated that the lowest LC50 was that of Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 88 publications
1
10
0
Order By: Relevance
“…These findings are in line with the results demonstrated by Silva et al (2019), where Solanum stipulaceum root and Ramalina aspera lichen extracts recorded low toxicity on A. salina , despite being molluscicidally effective on Biomphalaria glabrata . This matches also with the findings of Saleh et al (2022), although they recorded higher mortality rates of A. salina nauplii exposed to Scenedesmus obliquus and Spirulina platensis extracts (30% and 33% respectively), and they reported that the effective concentrations of these algal extracts on B. alexandrina snails were safe on other non‐target aquatic organisms. Ultimately, B. aerius and B. toyonensis extracts can be tested on a larger scale, such as in semi‐field conditions to determine their efficiency as molluscicides under different environmental conditions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in line with the results demonstrated by Silva et al (2019), where Solanum stipulaceum root and Ramalina aspera lichen extracts recorded low toxicity on A. salina , despite being molluscicidally effective on Biomphalaria glabrata . This matches also with the findings of Saleh et al (2022), although they recorded higher mortality rates of A. salina nauplii exposed to Scenedesmus obliquus and Spirulina platensis extracts (30% and 33% respectively), and they reported that the effective concentrations of these algal extracts on B. alexandrina snails were safe on other non‐target aquatic organisms. Ultimately, B. aerius and B. toyonensis extracts can be tested on a larger scale, such as in semi‐field conditions to determine their efficiency as molluscicides under different environmental conditions.…”
Section: Discussionsupporting
confidence: 91%
“…In this context, biological control of B. alexandrina snails has been used to eliminate the transmission of schistosomiasis disease (Inobaya et al, 2014; Secor, 2014). Biological control includes algae, bacteria, fungi and plants that have been demonstrated to have molluscicidal activities against different snail species (Duval et al, 2015; Ibrahim et al, 2021; Molla et al, 2013; Saleh et al, 2022). Some studies have investigated bacteria as biocontrol agents against snails (de Oliveira et al, 2004; Duval et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“… [25] and Saleh et al . [26] , a brine shrimp toxicity test was performed on the bio-synthesized ZnO_G240 nanoparticle concentrations. 3.3 g of instant ocean sea salt (Aquarium System, Ohio) was dissolved in 100 mL of distilled water, and 0.5 g of the dried cysts of Artemia salina (Linnaeus) nauplii was added to the salt solution and incubated at room temperature under continuous aeration and illumination.…”
Section: Methodsmentioning
confidence: 99%
“…The biomass of Chlorella sp. was waterextracted using a modification as described in Somasekharan et al [27] and Saleh et al, [28]. In brief:one gram of dried and grounded Chlorella biomass was suspended in a glass tube containing 20 mL of dH 2 O and extracted in a water bath sonicator at 50 ˚C for 30 min.…”
Section: Aqueous Extracts Of the Microalgamentioning
confidence: 99%